Global Value Chain and International Alliance Strategy: Analysis of Local Cocoa Commodities from West Sulawesi in the International Market - Abbas, Wandi; Losi, Zainuddin (PT Mattawang Mediatama Solution, 2025)
The lower cost of trade between countries has led to increased trade activities with the Global Value Chains (GVC) scheme and the International Alliance Strategy which have been proven to provide many benefits for countries, including accelerated industrialization, technology transfer, employment absorption, and increased industrial value. Participation in GVC consists of two components, forward and backward participation, which have different characteristics. This study aims to identify the analysis of GVC strategies for primary commodities of West Sulawesi cocoa in the international market. The study was conducted using qualitative methods and international trade theory and the Global Value Chain approach using literature studies and interviews. The location of the study was Polewali Mandar Regency, West Sulawesi, one of the provinces with the largest cocoa production in Indonesia. The results of this study indicate that in the supply chain, collaboration and cooperation are very significant from various stakeholders, both from the government, entrepreneurs in this case Barry Callebaut, Cocoa Horizon, PT Bumi Surya Selaras